CD44 expression in pleomorphic adenoma, carcinoma ex pleomorphic adenoma and their adjacent normal salivary glands - Nafiseh Shamloo; Nasim Taghavi; Farzad Yazdani; Soudeh Shalpoush; Samane Ahmadi (Wolters Kluwer Medknow Publications, 2018)
Background: CD44 is a transmembranous proteoglycan, with a main role of cell adhesion to other cells and to extracellular matrix involved in the preservation of three-dimensional structure of organs. Pleomorphic adenoma (PA) is a common benign salivary gland tumor, composed of myoepithelial and ductal components. Carcinoma ex-PA (CXPA) is malignant transformation of the epithelial elements in PA. The aim of this study was to evaluate CD44 expression by immunohistochemistry in these two tumors and normal salivary gland near these tumors. Materials and Methods: In this cross-sectional immunohistochemical study, 40 paraffin blocks (formalin fixed, paraffin embedded) with thirty belonging to PA and ten blocks of CXPA and 18 paraffinized blocks of normal salivary glands' tissue adjacent to tumoral tissue (13 in the vicinity of PA and 5 in the vicinity of CXPA) were selected. Immunohistochemical expression of CD44 was observed and compared with each other. For data analysis, we used Chi-square, Kruskal-Wallis, and Mann-Whitney tests and the quantity of P values was considered 0.05. Results: There was a significant difference in CD44 expression frequency between PA, CXPA, and normal salivary glands with higher expression noted in CXPA. Furthermore, expression frequency of CD44 in adjacent normal salivary gland of CXPA was significantly higher than PA. There was no significant difference in the expression of CD44 with respect to lymph node metastasis. Conclusion: Higher expression of CD44 in CXPA might illustrate CD44's role in malignant transformation of PA.